2022
DOI: 10.31004/basicedu.v6i3.2196
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kebugaran Jasmani, Status Gizi, dan Motivasi Belajar terhadap Hasil Belajar PJOK

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh kebugaran jasmani, status gizi, dan motivasi belajar terhadap hasil belajar PJOK di SD Islam Terpadu Fathur Rahman Tembilahan. Jenis penelitian yaitu kuantitatif mengunakan disain penelitian korelasi dengan metode asosiatif kausal. Populasi dalam penelitian ini berjumlah 56 orang.Teknik pengambilan sampel menggunakan total sampling, yaitu seluruh populasi dijadikan sebagai sampel penelitian. Untuk mengukur data kebugaran jasmani menggunakan Tes Kebugaran Jasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…(Kurniasari, 2017) that if it can be concluded that there is no relationship between the level of education, employment and parental income with the nutritional status of students related to the results of children's learning intelligence. (Idham, Neldi, Komaini, Sin, & Damrah, 2022) revealed that if there is a direct influence between physical fitness on learning outcomes of 7.2%, there is a direct influence between nutritional status on learning outcomes of 9.7%, there is an influence between social status and nutrition for children followed by learning outcomes achieved 7.2% (Putri, Rahayu, & Maemunah, 2017) The results showed that almost half the education of the respondent's father was a bachelor, namely 15 people (35.7%); almost half of the respondents' mothers education was undergraduate, namely 15 people (35.7%). almost half of the respondent's father's work is private, namely 15 people (35.7%): most of the respondents' mothers do not work, namely 28 people (66.7%) and most of the 93.9% children have normal nutrition.…”
Section: Relationship Between Nutritional Status and Economic Status ...mentioning
confidence: 99%
“…(Kurniasari, 2017) that if it can be concluded that there is no relationship between the level of education, employment and parental income with the nutritional status of students related to the results of children's learning intelligence. (Idham, Neldi, Komaini, Sin, & Damrah, 2022) revealed that if there is a direct influence between physical fitness on learning outcomes of 7.2%, there is a direct influence between nutritional status on learning outcomes of 9.7%, there is an influence between social status and nutrition for children followed by learning outcomes achieved 7.2% (Putri, Rahayu, & Maemunah, 2017) The results showed that almost half the education of the respondent's father was a bachelor, namely 15 people (35.7%); almost half of the respondents' mothers education was undergraduate, namely 15 people (35.7%). almost half of the respondent's father's work is private, namely 15 people (35.7%): most of the respondents' mothers do not work, namely 28 people (66.7%) and most of the 93.9% children have normal nutrition.…”
Section: Relationship Between Nutritional Status and Economic Status ...mentioning
confidence: 99%
“…Menurut Idham et al (2022) faktor pola makan dan kesehatan siswa dapat memberi dampak terhadap aktivitas siswa saat mengikuti pembelajaran. Sesuai dengan fungsinya bahwa motivasi sebagai pendorong siswa untuk melakukan suatu tindakan yang didasari oleh keinginannya sendiri maupun adanya pengaruh dari luar.…”
Section: Pendahuluanunclassified
“…Parents and schools are responsible for ensuring that students have a balanced diet. (Idham et al, 2022). Physical fitness is the goal of one of the implementations of sports and health physical education subjects, physical fitness functions as an integrated component of the broader education system, focusing on developing moral behavior, mental and emotional stability, and social and emotional abilities through activities physique.…”
Section: Introductionmentioning
confidence: 99%